The chloride corrosion of marine concrete - SHALYI EVGENYI; KIM LEV (Zenodo, 2018)
Chloride aggression is one of the main causes of reinforcement corrosion in concrete structures, especially in offshore and coastal structures. Chloride ion penetration due to capillary absorption and diffusion destroys the passivating protective film on the reinforcement, resulting in rapid destruction of the protective layer of concrete. In the present study, the chloride ion diffusion model has been improved and the durability analysis software has been developed. The chloride ion concentration is modelled depending on the service life and climatic conditions. Model verification was performed to solve the problem of chloride concentration determination in the concrete protective layer of hydraulic structures. Chloride ions have the greatest activation ability of all types of anions. They destroy the passivating film on the surface of the reinforcement in places where the concentration reaches a critical value (typically 0.4% by weight of cement, EN 206-1). The analysis of experimental data has demonstrated that the chloride-ion content in the samples exceeds the critical value. A good convergence of the experimental data with the data on a finite-difference model has been obtained. The results demonstrate that the proposed software enables one to determine the impact of each parameter on the result. The model has been verified with the data of the field surveys carried out by the authors in the port facilities of Sakhalin Island. It has been shown that, as to those facilities locally, evident is the concentration limit for chloride in the zone of reinforcement which is subject to corrosion. Further researches are aimed at collecting factual materials in the ports of the entire Russian Far East.